Pengaruh Kompetensi Sumber Daya Manusia Dalam Peningkatan Kinerja Pegawai Studi Kasus Pada Pemerintah Desa Popongan - Dhani Nur Hidayat (Universitas 17 Agustus 1945 Semarang, 2023)
Superior human resources are needed by the village government in village development. The role of human resources is very strategic and important in achieving organizational goals. Therefore, improving the quality of human resources needs to be carried out by the village government. Skilled and expert human resources certainly have good performance and can help realize village development. The purpose of this research is to find out and analyze how the influence of human resource competence in improving employee performance is a case study in the Popongan Village Government. In this study using qualitative research with a qualitative descriptive approach. The analysis used in this study is to use SWOT analysis, which analyzes Strengths, Weaknesses, Opportunities and Threaths. This study found that the Popongan Village Government has strengths and opportunities that can improve employee performance. However, on the other hand it also has weaknesses and threats that can reduce employee performance. Then it is necessary to apply the right strategy to increase strengths and opportunities and reduce weaknesses and threats